2002
DOI: 10.1227/01.neu.0000309115.09463.7d
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable Valves in Normal-pressure Hydrocephalus: A Retrospective Study of 218 Patients

Abstract: Noninvasive, particularly consecutive, minor or single larger adjustments to the valve opening pressure can further improve outcome in patients with NPH who undergo shunting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 32 publications
5
36
2
Order By: Relevance
“…Even with the use of programmable valves, modern iNPH series have reported non-traumatic subdural hematoma rates as high as 10%, with up to 7% requiring surgical evacuation. 12,18 In contrast, we have demonstrated no incidence of subdural hematoma or hygroma in 33 iNPH patients undergoing LP shunt placement, and we previously reported a series of 74 patients undergoing LP shunt placement for various CSF disorders with no patients with subdural hematoma or acquired Chiari malformations. 21 Additionally, the risk of symptomatic intraparenchymal hematoma from ventricular catheter placement, occurring in approximately 1% of patients with NPH, does not exist for LP shunt placement.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Even with the use of programmable valves, modern iNPH series have reported non-traumatic subdural hematoma rates as high as 10%, with up to 7% requiring surgical evacuation. 12,18 In contrast, we have demonstrated no incidence of subdural hematoma or hygroma in 33 iNPH patients undergoing LP shunt placement, and we previously reported a series of 74 patients undergoing LP shunt placement for various CSF disorders with no patients with subdural hematoma or acquired Chiari malformations. 21 Additionally, the risk of symptomatic intraparenchymal hematoma from ventricular catheter placement, occurring in approximately 1% of patients with NPH, does not exist for LP shunt placement.…”
Section: Discussionmentioning
confidence: 83%
“…The risk of immediate intraparenchymal hematoma from ventricular catheter insertion or delayed subdural hematoma from overdrainage can be significant, and may be worse in NPH patients due to decreased brain elasticity and subdural space expansion when the lateral ventricles are collapsed by overdrainage. 18 The Dutch NPH Study reported subdural hematoma and hygroma rates as high as 71% in patients with low-pressure valves. 19 Since the 1990s overdrainage has been addressed with the use of programmable VP shunt valves, which can be adjusted in response to low-pressure symptoms or subdural fluid collection formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This high incidence of overdrainage can be reduced with the use of adjustable differential pressure valves. In their studies on adult hydrocephalic patients with adjustable differential pressure valves, Bret et al (1999), Kay et al (2000), and Zemack and Romner (2002) reported subdural effusions as a result of overdrainage in 6.9-27% of cases [6,17,29]. Chong et al (2002) studied the use of a flow-regulated ASD in combination with a fixed low-pressure valve in adult patients, and reported no cases of overdrainage [8].…”
Section: Discussionmentioning
confidence: 99%